1996
DOI: 10.1016/s0741-5214(96)80004-8
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking increases the development of intimal hyperplasia after vascular injury

Abstract: Inhalation of cigarette smoke increases the development of intimal hyperplasia in a rat model of a balloon catheter arterial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…CS exposure in WT mice was associated with increased arterial iNOS expression, superoxide production, activator protein-1 (AP-1) activation, and serum NO. 4,5 In the Atherosclerosis Risk in Communities Study, active smoking and exposure to environmental tobacco smoke were associated with accelerated progression of intimal/medial thickness of the carotid artery. 6 The underlying mechanism(s) of these deleterious effects remain unknown.…”
mentioning
confidence: 99%
“…CS exposure in WT mice was associated with increased arterial iNOS expression, superoxide production, activator protein-1 (AP-1) activation, and serum NO. 4,5 In the Atherosclerosis Risk in Communities Study, active smoking and exposure to environmental tobacco smoke were associated with accelerated progression of intimal/medial thickness of the carotid artery. 6 The underlying mechanism(s) of these deleterious effects remain unknown.…”
mentioning
confidence: 99%
“…Our previous studies in the rat carotid artery demonstrated an increase in neointimal hyperplasia in this deendothelialized model [9,23]. Thus in two distinct models of arterial injury, this method of cigarette smoke exposure causes an increase in smooth muscle growth as well as endothelial regrowth.…”
Section: Figmentioning
confidence: 59%
“…This is caused by invasion and proliferation of smooth muscle cells, fibroblasts and matrix material derived from the cut end of the host artery. It has been reported that the risk factors for the genesis and development of atherosclerosis, such as smoking, diabetes, harvesting and preparation of the vein grafts, are important factors [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Although the factors that lead to myointimal hyperplasia in arterial vein grafts are unknown, growth factors like platelet-derived growth factor are powerful mitogens for smooth muscle cells that have been implicated in the genesis of myointimal hyperplasia [2,9,[12][13][14]. Sterpetti et al [2] observed in a rat model that myointimal hyperplasia formation and regression in experimental vein grafts correlate with growth factor production.…”
Section: Discussionmentioning
confidence: 99%